2020
DOI: 10.1101/2020.02.24.962787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERECTA family signaling constrainsCLAVATA3andWUSCHELto the center of the shoot apical meristem

Abstract: 2 Summary statementERf signaling restricts the width of the shoot apical meristem, a structure which generates aboveground plant organs, by inhibiting expression of two principal regulators, CLV3 and WUS, at its periphery. Abstract: The shoot apical meristem (SAM) is a reservoir of stem cells that gives rise to all post-embryonic aboveground plant organs. The size of the SAM remains stable over time due to a precise balance of stem cell replenishment versus cell incorporation into organ primordia. The WUSCHEL … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In [42] it is discussed that a dose-dependent inhibitory effect of WUS on proliferation rates may play a role in this context. Furthermore, ERECTA signalling may be involved in confining the WUS and CLV3 expression to the meristem centre by repressing both signals [48,49]. These mechanisms could be compared in future extension of our model.…”
Section: Discussionmentioning
confidence: 98%
“…In [42] it is discussed that a dose-dependent inhibitory effect of WUS on proliferation rates may play a role in this context. Furthermore, ERECTA signalling may be involved in confining the WUS and CLV3 expression to the meristem centre by repressing both signals [48,49]. These mechanisms could be compared in future extension of our model.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, in A. thaliana the close homologs EPFL4 and EPFL6 have been shown to have distinct functions in inflorescence growth 62 , 63 . However, two very recent studies revealed that EPFL4 and EPFL6 are also expressed in the periphery of the shoot apical meristem (SAM) and function redundantly with EPFL1 and EPFL2 to regulate the meristem size and leaf initiation 64 , 65 . In particular, signaling downstream of EFPL ligands and their receptors confines the WUS-CLV3 pathway to the center of the SAM by inhibiting its expression in the meristem periphery 65 .…”
Section: Resultsmentioning
confidence: 99%
“…However, two very recent studies revealed that EPFL4 and EPFL6 are also expressed in the periphery of the shoot apical meristem (SAM) and function redundantly with EPFL1 and EPFL2 to regulate the meristem size and leaf initiation 64 , 65 . In particular, signaling downstream of EFPL ligands and their receptors confines the WUS-CLV3 pathway to the center of the SAM by inhibiting its expression in the meristem periphery 65 . In this regard, it is especially interesting that AqEPFL4 came out as one of the most connected hub genes in a module that is strongly associated with s1, suggesting that our results provide further evidence for the role of the EPFLs in the meristem homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…In [ 41 ] it is discussed that a dose-dependent inhibitory effect of WUS on proliferation rates may play a role in this context. Furthermore, ERECTA signalling may be involved in confining the WUS and CLV3 expression to the meristem centre by repressing both signals [ 48 , 49 ]. These mechanisms could be compared in future extension of our model.…”
Section: Discussionmentioning
confidence: 99%